The Application and Challenge of Chinese Folk Literature in International Chinese Language Education Under The Background of The Belt and Road Initiative: 一带一路 背景下中国民间文学在国际汉语教育中的应用与挑战 - Shan Shan, Li (Published by Confucius Institute UNS, 2024)
With the promotion of the